E-Lelang Barang Antik Berbasis Mobile Pada Komunitas Pecinta Antik Kreatif Sriwijaya Palembang Menggunakan Metode Mobile-D - Nurul Adha Oktarini Saputri; Elma Amorita; Prihambodo Hendro Saksono (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
At this time antiques are increasingly in demand by many people.in Kompaks (Sriwijaya creative antique lovers community) Palembang introduces the history of these antiques such as furniture, weapons, art items, household items and other art items.besides that, compact also conducts antique auction.Antiques auction is done at the compact post itself and also at events related to history and antiques.from the auction process the time needed for the auction to be compact is longer and bidders must visit the tender process location and follow all the process activities that take place. With these problems, the researcher will make an e-auction (electronic auction) antiques application that will work according to the established auction rules. This e-auction application uses the mobile-D method which is one method that is suitable for the development of mobile applications because it is agile and flexible. so with this application it is expected to make it easier to conduct auction activities that are not limited by time and place.